Kemampuan Penalaran Statistik Mahasiswa dalam Pembelajaran Statistik Menggunakan Model Flipped Classroom Berbasis SPSS dan STATCAL: Studi Eksperimen - Ramadhani, Rahmi (TIN: Terapan Informatika Nusantara, 2021)
Statistical reasoning skills are an essential ability for students to develop so that the solving of statistical problems can be solved optimally and adequately. Students can improve their statistical reasoning skills by using learning that gives them new experiences and teaches them how to utilize proper statistical analysis to address statistical challenges in student science research. One of the learning models recommended in this study is the flipped classroom model. Flipped classroom model is a learning model that combines two learning conditions, namely conditions in the classroom and conditions outside the school. Flipped classroom models are also effectively used in learning during the Covid-19 pandemic. Learning that combines two learning conditions can maximize learning effectiveness even if implemented in the phase of technology-based distance learning. The implementation of flipped classroom model is also effective if integrated with supporting learning media, namely SPSS and STATCAL applications. Based on this, the purpose of this study is to see the improvement of students' statistical reasoning skills in statistical learning taught using flipped classroom models based on SPSS and STATCAL. This research is a quasi-experimental study with the type of pretest-posttest control group design. The sample of this study is a 2nd-grade student at the University of The Main Potential. Homogeneous and normally distributed research data was further tested using the T-Independent Sample T-Test hypothesis test. The results showed that students' statistical reasoning abilities improved, and the SPSS and STATCAL-based classroom flipped models proved effective in enhancing students' statistical reasoning abilities